Enhancement of Compressive Strength Following Preheating of Universal Single-Shade Resin Composite - Athallah, Malsha Yuniza; Mozartha, Martha; Merdekawati, Listia Eka (FKG Universitas Syiah Kuala, 2025)
The development of restorative materials presents a universal single-shade resin composite claimed to match all tooth colors. In addition to aesthetics, composite resin must have good mechanical properties. The temperature factor affects the polymerization, which will affect the compressive strength. The purpose of study was to investigate the effect of preheating on the compressive strength of single-shade universal resin composite. Universal single-shade resin composite was used to make cylindrical specimens with a diameter of 3 mm and a thickness of 6 mm and divided into two groups: with and without preheating (n=9). Specimens of preheating groups were prepared by heating the resin composite in a heater device at 600C for 15 minutes, then placed in the mold and irradiated using a light curing unit with an intensity of 2300 mW/cm for 6 seconds and then polished using composite polishing kits. The compressive strength was tested using a universal testing machine. The data obtained were analyzed using an independent t-test. The result of study showed the mean compressive strength values were significantly higher in the preheated group than in the non-preheated group (p0.05). The conclusion of this study was preheating universal single-shade resin composite to 60 degrees Celsius significantly enhances its compressive strength.